The Difference of Fish Catches by Using “Jaring Insang” (Gill Nets) Before and After Midnight in Nagari Tikalak (Tikalak Village), X Koto Singkarak, Solok Regency, West Sumatera - Oka Mahendra; Bustari '; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractThis research was conducted on August 2014 at Nagari Tikalak, X Koto Singkarang, Solok Regency, West Sumatera. Its objection is to know the overall comparison of fish catches (kg), to know types and the result of fish catches (how many fish can be catched) at before and after midnight fishing by using “gill nets”. This reseach uses survey method. The operation of gill nets had been done for 10 days.Fish catches on before midnight was “Bilih fish” (4,78 kg / 692 fish), “Paweh fish” (0,07 kg / 7 fish), and “Hampala fish” (0,05 kg / 4 fish). Whereas on after midnight fishing, the fisherman could get 9,18 kg (1430 fish)Bilih fish and 0,13 kg (8 fish)Paweh fish. Overall, there were 3 types fish which were captured;Bilih fish (Mystacoleusus padangensis Blkr), Paweh fish (Osteochilus brachmoides) andHampala fish (Hampala mocrolepidota).Based on counting result by using T test and chi square test, I found that there were the divergence of fish catches between before midnight fishing and after midnight fishing.Keywords: gillnets, before midnight, after midnight, West Sumatera